2018
DOI: 10.1038/s41598-018-20424-y
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of low alcohol exposure, but adverse effects of high alcohol intake on glymphatic function

Abstract: Prolonged intake of excessive amounts of ethanol is known to have adverse effects on the central nervous system (CNS). Here we investigated the effects of acute and chronic ethanol exposure and withdrawal from chronic ethanol exposure on glymphatic function, which is a brain-wide metabolite clearance system connected to the peripheral lymphatic system. Acute and chronic exposure to 1.5 g/kg (binge level) ethanol dramatically suppressed glymphatic function in awake mice. Chronic exposure to 1.5 g/kg ethanol inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 76 publications
(91 reference statements)
1
86
0
1
Order By: Relevance
“…Our group has shown that in a rat model of TBI and binge alcohol, recovery in a skilled sensorimotor task was slower and the recovery plateau was lower in alcohol-exposed animals (Vaagenes et al, 2015) as also reported in clinical studies (Corrigan, 1995;Gurney et al, 1992;Joseph et al, 2015;Schutte & Hanks, 2010) although others have found a benefit (Chandrasekar et al, 2018(Chandrasekar et al, , 2017Lundgaard et al, 2018).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our group has shown that in a rat model of TBI and binge alcohol, recovery in a skilled sensorimotor task was slower and the recovery plateau was lower in alcohol-exposed animals (Vaagenes et al, 2015) as also reported in clinical studies (Corrigan, 1995;Gurney et al, 1992;Joseph et al, 2015;Schutte & Hanks, 2010) although others have found a benefit (Chandrasekar et al, 2018(Chandrasekar et al, , 2017Lundgaard et al, 2018).…”
Section: Introductionsupporting
confidence: 61%
“…The National Institute on Alcohol Abuse and Alcoholism (NIAAA) defines binge drinking as a mode of consumption that results in a BAL of greater than 80 mg/dl, which is typically achieved by having five drinks for men and four drinks for women in two hours (Olthuis, Zamboanga, Ham, & Tyne, ). Our group has shown that in a rat model of TBI and binge alcohol, recovery in a skilled sensorimotor task was slower and the recovery plateau was lower in alcohol‐exposed animals (Vaagenes et al, ) as also reported in clinical studies (Corrigan, ; Gurney et al, ; Joseph et al, ; Schutte & Hanks, ) although others have found a benefit (Chandrasekar et al, ; Lundgaard et al, ).…”
Section: Introductionmentioning
confidence: 68%
“…The polarization of AQP4 along vessels in tissue was quantified in cortex and hippocampus ( Kress et al, 2014 ; Lundgaard et al, 2018 ). Blood vessels were selected at random on confocal images and marked cross-sectionally using the line plot tool in ImageJ to include AQP4 signal from vascular endfeet and from the surrounding parenchyma.…”
Section: Methodsmentioning
confidence: 99%
“…The question of whether the APOE-4 allele influences the protective effect of moderate ethanol intake on cognitive risk has not yet been resolved [58]. A glymphatic system [67] formed by astroglial cells was discovered in the central nervous system, which may eliminate soluble proteins and metabolites and plays a key role in the clearance of proteins that are potentially neurotoxic, such as Aβ18 and Tau23. The effect of acute and chronic exposure to ethanol on glymphatic function was investigated.…”
Section: Moderate Alcohol Consumptionmentioning
confidence: 99%